Tumor Imaging: Radiopharmaceuticals and Fluorescein Sodium Mediated Triple‐Modality Molecular Imaging Allows Precise Image‐Guided Tumor Surgery (Adv. Sci. 13/2019). Issue 13 (3rd July 2019) - Zheng, Sheng; Zhang, Zeyu; Qu, Yawei; Zhang, Xiaojun; Guo, Hongbo; Shi, Xiaojing; Cai, Meishan; Cao, Caiguang; Hu, Zhenhua; Liu, Haifeng; Tian, Jie
Abstract : Aiming to achieve precise tumor surgery, Zhenhua Hu, Haifeng Liu, Jie Tian, and co‐workers develop a multimodality in vivo imaging strategy combining nuclear imaging, optical imaging and microscopy. High performance is achieved in tumor detection and surgical navigation using clinically approved agents. This strategy based on Cherenkov excited fluorescent imaging demonstrates high clinical translational potential and opens a new direction for surgical navigation research.